2015
DOI: 10.1177/0143624415615533
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric cooling heating unit prototype

Abstract: The article describes from an architectonical point of view the design, assembly, and energy behavior of a prototype for air-conditioning in residential buildings using Peltier cells, which means the application in the field of construction of a technology used in very specific areas. The new system has been designed as an independent, prefabricated, modular construction element that must fit perfectly between the structural floors and is easily adapted to the demands of different buildings. The thermoelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This work contributes in identifying the key aspect that may increase the efficiency of the HVAC systems in ventilated façades. Also, this research completes the authors' previous work [33][34][35][36][37] about the theoretical design and construction of an active ventilated façade with Peltier modules. The authors are aware that a techno-economic analysis of a THU prototype has not yet been reported.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…This work contributes in identifying the key aspect that may increase the efficiency of the HVAC systems in ventilated façades. Also, this research completes the authors' previous work [33][34][35][36][37] about the theoretical design and construction of an active ventilated façade with Peltier modules. The authors are aware that a techno-economic analysis of a THU prototype has not yet been reported.…”
Section: Introductionsupporting
confidence: 82%
“…The result was the construction of a simplified inhabited housing unit (prefabricated module) with a thermoelectric heating system. A detailed report on this first THU version (v1.1) and its manufacture has been presented by the authors in previous works [33][34][35][36]. This section provides a brief description of this first version and presents the improvement of this prototype (THU v1.2).…”
Section: Technical Description Of the Thermoelectric Heating Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the emerging applications of TE systems is the use of Peltier modules for building cooling and heating, either through integration into building envelope or as separate units [16]. Various configurations have been proposed and studied for integrated TE modules in windows [17][18][19][20] and walls [17,[21][22][23][24][25] demonstrated promising results. A few previous studies have also been focused on incorporating TE modules in the ceiling.…”
Section: Introductionmentioning
confidence: 99%
“…More recent applications use TEC with different prototype design for refrigeration system (Martin-Gomez et al, 2016, Martinez, 2016. Vadi and Kulkarni, 2015 presented analysis of thermoelectric cooler performance using two modules connected in parallel, with Peltier module of 231W, 15.4V, 15A, TEC1-12715.…”
Section: Introductionmentioning
confidence: 99%